Dynamic hand and finger load distribution patterns in the first year following surgically treated distal radius fracture - Johannes Karnatz; Christoph Harms; Dagmar-Christiane Fischer; Thomas Mittlmeier (BMC Musculoskeletal Disorders)
Abstract Background Manugraphy is a relatively young technique for assessing dynamic load distribution when gripping a cylinder. Thereby, dynamic hand grip function is objectivated, providing a more detailed insight than with other clinical assessment tools. Analysis of changes in grip patterns following a distal radius fracture provides a new perspective on documenting the recovery process of this common injury. Our aim was also to investigate the relationships between load distribution during a maximum force grip and other hand function parameters to better understand the implications for follow-up and rehabilitation. Methods Assessment of the QuickDASH score, finger and wrist range of motion, grip strength as well as grip load distribution using manugraphy was performed 3, 6 and 12 months following isolated surgically treated distal radius fractures. Using special software, each finger ray as well as the thenar and hypothenar were defined on the digital pressure map and the contribution to the total force was calculated for each region. Results After 3 months, 49 patients participated in the follow-up examinations, after 6 months 38 patients and after 12 months 35 patients. When the QuickDASH score decreased significantly, the wrist range of motion and grip strength recovered to more than 90% of the values of the uninjured side within the first year after fracture treatment. The cumulative analysis of the load distribution showed that after 3 months, the thumb and index finger exerted a greater proportion of the total grip strength than did the uninjured hand, whereas the contributions of the thenar and hypothenar were smaller. These changes diminished at 6 and 12 months, respectively. The changes in grip pattern showed significant correlations with grip strength and partly with range of motion of finger and wrist as well as the QuickDASH score. Conclusions The dependence between changes in load distribution and different hand function parameters implies the particular additional value and validity of this helpful technique for individual assessment and rehabilitation of hand function. Early detection of persisting imbalances of dynamic load distribution might support clinical decision-making in the postoperative course during rehabilitation.